Does income transparency affect support for redistribution? Evidence from Finland's tax day - Maurice Dunaiski; Janne Tukiainen (Aboa Centre for Economics (ACE), 2023)
This paper examines whether income transparency - the public release of citizens' income information - affects support for redistribution. We leverage a quasi-experiment in Finland, where every year on the so-called tax day, the authorities release income information on Finland's top earners to the public. To identify causal effects we compare respondents who took part in the European Social Survey shortly before and after the event. We find that the tax day increases perceptions that earnings of the top 10% are unfair, but that public support for redistribution remains largely unaffected. A notable exception are top earners, who decrease their support for redistribution, and young people, who increase their support for redistribution. Our results highlight the scope conditions of previous experimental studies, and suggest that increasing exposure to inequality through a real-world policy, rather than experimental treatments, may trigger only marginal changes in support for redistribution.
Keywords: D31; D63; D72; D80; H20; H23; H24; H31; 330; income transparency; inequality; redistribution; taxes